PENGEMBANGAN MODUL PRAKTIKUM UNTUK MODULATOR OPTIK INTERNAL DAN EKSTERNAL - Aini, Nurulita; Sudiarta, Pande Ketut; Putra Sastra, Nyoman (Jurnal SPEKTRUM; Vol 8 No 1 (2021): Jurnal SPEKTRUM, 2021)
The optical modulator is a component used to convert information signals into a carrier signal in the form of a light beam. 3 optical modulators are widely used, namely the internal modulator, the machzehnder modulator (MZM), and the electro-absorption modulator (EAM). Each optical modulator has advantages and disadvantages, but in general, the purpose of an optical modulator is to modulate light beams. The purpose of this study was to determine the performance comparison of the internal and external optical modulator and the feasibility of the practicum module. The method used is to simulate an optical modulator on a fiber-optic network using Optisystem software. The network feasibility parameters analyzed were Q-factor, BER, and eye diagram until performance reached the ITU-T G.984.2 standard with a minimum limit of Q-factor = 6 and BER 10-9. The optical modulator changes internal and external variables. The feasibility test of the practicum module uses the method of filling out a questionnaire with a Likert scale of 1–5 and giving pre-test and post-test to the practitioner. The comparison of optical modulator performance shows that MZM performance is better than EAM and internal modulator. In the bit rate test, the transmission distance used is 65 km, and signal power of +7 dBm MZM is capable of sending bit rates of up to 27 Gbps. In testing the transmission distance, the bit rate used is 10 Gbps, and signal power of +7 dBm MZM can cover a distance of up to 70 km. In the signal power test, the bit rate used is 10 Gbps and the transmission distance is 65 km MZM capable of working at +5 dBm signal power. This practicum module is very feasible as teaching material according to the percentage of the practitioner's assessment of 88.2%.